The effect of integrated marketing communication, brand image and experiential marketing on customer satisfaction - Astri, Astri; Nasution, Juliana; Syafina, Laylan (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2024)
This study aimed to determine the effects of integrated marketing communication, brand image, and experiential marketing on the satisfaction of Sharia Bank customers. The research used a survey method to collect data from 92 customers. The results indicate that the influence of integrated marketing communication, brand image, and experiential marketing is important for customer satisfaction. These findings illustrate that integrated marketing communication, brand image, and experiential marketing enhance customer satisfaction. The results have important implications, particularly for marketing strategies and customer management practices. Public interest statements This research is highly relevant for all banks as it highlights the influence of integrated marketing communication, brand image, and experiential marketing on customer satisfaction. Understanding these factors can help banks enhance their marketing strategies and improve customer experiences, ultimately increasing customer satisfaction and loyalty. Article info: Received 6/29/2024 | Revised: 9/21/2024 | Accepted: 9/23/2024 | Online First 9/28/2024